Association of Active and Passive Coping Strategies with Neck Pain among Dentists of Lahore - Fariha Asghar, Sadia Chaudhary, Fatima Aslam, Hafiz Muddassir Riaz, Muhammad Saqib Rabbani, Sajid Mehmood, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Dentists are at increased risk of musculoskeletal problems due to many reasons that include stress and their posture during working time. Aim: To determine the association between coping strategies and disabling neck pain among dentists working in different hospitals in Lahore, Pakistan. Study Design: Cross sectional study. Methodology: non-probability consecutive sampling was undertaken among 134 dentists employed at various hospitals in Lahore. To identify the coping mechanisms, we employed the Vanderbilt Pain Management Inventory and the Visual Analog Scale for Chronic Pain. Data was evaluated by using SPSS version 23. The Chi-square test was used to determine the association of coping strategies and neck pain. Results: In the study sample of 134 responders, 111 people experienced significant neck pain. The emergence of incapacitating neck pain was substantially correlated with passive coping. Conclusion: It was concluded that severe neck pain was strongly associated with passive coping strategies. Key words: Coping, Disabling Neck Pain and Dentistry.